Korelasi Keterampilan Memirsa Teks Berita Dengan Keterampilan Menulis Teks Berita Siswa Kelas VII SMP Negeri 2 Gunung Talang - Riri Angraini; Yulianti Rasyid; Mohammad Hafrison; Nofrahadi Nofrahadi (Universitas Pakuan, 2026)
The Correlation Between News Text Viewing Skills and News Text Writing Skills Among Grade VII Students at SMP Negeri 2 Gunung Talang This study aims to describe the following: first, the news text writing skills of Grade VII students at SMP Negeri 2 Gunung Talang; second, the news text viewing skills of Grade VII students at SMP Negeri 2 Gunung Talang; and third, the significance of the correlation between news text viewing skills and news text writing skills among Grade VII students at SMP Negeri 2 Gunung Talang. This is a quantitative study employing a descriptive-correlational method. The study population consisted of 311 Grade VII students at SMP Negeri 2 Gunung Talang, with a sample size of 62 students. The sample was selected using a simple random sampling technique, representing 20% ​​of the total population. The research instruments consisted of two tests: an objective test for news text viewing skills and a performance test for news text writing skills. The study yielded three results. First, the news text viewing skills of Grade VII students at SMP Negeri 2 Gunung Talang were rated as